Improving Purchase Decisions In Pandemic Times Through Expected Value By Analyzing Direct Selling And Sales Promotion at CV. Dunia Unggas - Emil Salim; Nina Gusmala Delvi (Journal Of Science Education And Management Business, 2022)
In this study are consumers who are in West Sumatra. Sampling using Double sampling technique namely Quota Sampling and Purposive Sampling.Based on the results of parisial research (t test) shows that there is a significant effect (0.042 <0.05) between direct selling on expected value, there is a significant effect (0.000 <0.05) between sales promotion on expected value, there is a significant influence significant (0.000 <0.05) between direct selling and sales promotion on expected value, there is an insignificant effect (0.100 <0.05) between direct selling on purchasing decisions, there is a significant effect (0.000 <0.05) between sales promotion on buying decision,There is a significant effect (0.001 <0.05) between expected value on purchasing decisions, There is a significant effect (0.005 <0.05) between direct selling and sales promotion on purchasing decisions with expected value as an intervening variable, the direct effect of direct selling (X1) is smaller than with the indirect effect of direct selling (X2 through expected value (Z) on purchasing decisions (Y), The direct effect of sales promotion (X1) is greater than the indirect effect of sales promotion (X2 through expected value (Z) on purchasing decisions (Y), the contribution of direct selling variables, sales promotion to expected value has an effect of 42.1%, the remaining 57 , 9% is influenced by other variables outside of this study, the contribution of direct selling, sales promotion variables to purchase decisions through expected value has an effect of 60.6%, the remaining 59.6% is influenced by other variables outside of this study.